2011
DOI: 10.5539/ijb.v3n2p153
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Antioxidant Potential of Nigerian Red Palm Oil (Elaeis Guineensis)

Abstract: Polyphenols have been shown in both in vitro and in vivo experiments to induce responses that are consistent with the protective effects of diets rich in fruits and vegetables against degenerative conditions such as cardiovascular disorders and cancer. Red palm oil, extracted from the fruit mesocarp of Elaeis guineensis is very important in the diet of many Nigerians, and indeed many citizens of developing countries living around the tropics. It contains antioxidant components such as carotenoids (alpha, beta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
15
1
Order By: Relevance
“…Canola oil contains about 0.53-0.97% plant sterols and about 700-1200 ppm tocopherols (Dupont et al 1989;Lin et al 2013). Palm oil is the richest natural plant source of lipid-soluble antioxidants such as carotenoids (aand b-carotenes, lycopenes), vitamin E (a-, b-, d-tocotrienols and tocopherol) and ubiquinone (Oguntibeju et al 2009;Atawodi et al 2011). Palm oil contains 44% oleic acid, 10% linoleic acid and about 40% palmitic acid (Siew & Ng 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Canola oil contains about 0.53-0.97% plant sterols and about 700-1200 ppm tocopherols (Dupont et al 1989;Lin et al 2013). Palm oil is the richest natural plant source of lipid-soluble antioxidants such as carotenoids (aand b-carotenes, lycopenes), vitamin E (a-, b-, d-tocotrienols and tocopherol) and ubiquinone (Oguntibeju et al 2009;Atawodi et al 2011). Palm oil contains 44% oleic acid, 10% linoleic acid and about 40% palmitic acid (Siew & Ng 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is unique in that it contains an equal amount of saturated and unsaturated fatty acids, with about 44% palmitic acid, 5% stearic acid (both saturated), 40% oleic acid (monounsaturated), 10% linoleic acid, and 0.4%   α -linoleic acid (both polyunsaturated), with natural fat soluble tocopherol, tocotrienol, and carotenoids which may act as antioxidants [38, 39]. Apart from the fat soluble antioxidants found in palm oil, studies have shown that RPO also contains several phenolic compounds, including gallic, chlorogenic, gentisic, coumaric, and caffeic acids, as well as catechins, hesperidin, narirutin, and 4-hydroxyl benzoate, all of which have appreciable radical scavenging and antioxidant ability [40–42]. The health benefits of RPO have been highlighted in feeding experiments using different animal models.…”
Section: Introductionmentioning
confidence: 99%
“…It contains lipid-soluble antioxidants such as carotenoids (α-and β-carotenes, lycopenes), vitamin E (in the form of α-, β-, δ-tocotrienols and tocopherol) and ubiquinone (Oguntibeju et al, 2009). Red palm oil is distinctive from other plant and animal oil because it contains 50% saturated fatty acids, 40% unsaturated fatty acids, and 10% polyunsaturated fatty acids (Atawodi et al, 2011). RPO has beneficial effects on arterial thrombosis and hypertension associated with oxidative stress (Edem, 2002;Narang et al, 2004) and is also protective against the consequences of ischemia /reperfusion injury (Esterhuyse et al, 2005, Bester et al, 2006.…”
Section: Introductionmentioning
confidence: 99%